Comparative Forms of Adjectives: the Semantic Classes and Syntactic Functions - Kristanti, Fransisca (Journal of Language and Literature, 2015)
The aim of the research is to identify the real-life distribution of the comparative forms of adjectives. This paper is a corpus-based analysis which discusses comparative forms of adjectives from the linguistics perspectives. British National Corpus (BNC) is used to collect the data due to the generality of the corpora. BNC contains the collection of both spoken and written language in various text types, thus, it represents language variety as a whole. The analysis is done using semantic and syntax approach. Downing’s and Locke’s (2006) theory on semantic classes and Quirk’s and Greenbaum’s (1973) theory on syntactic functions were applied. The analysis was done in cycles, and stopped at the third cycle due to the similar findings between cycles. Ninety out of two hundred sentences containing comparative adjectives were analyzed. The analysis results in several findings. First, both semantic classes, descriptors and classifiers, appear in the analysis of comparative adjectives. Yet, the most frequent occurrence is in the semantic class of descriptors. Second, there are four syntactic functions in which comparative adjectives occur and most of them function as pre-modifier of a noun phrase. This paper presents the initial step for further research on comparative adjectives based on the research of semantics and syntax. Further researches on how semantic classes influence syntactic functions is encouraged.